Movement and positioning of a virtual cuboid in 3d space in an augmented reality environment. - Ho, Yu-Hui; Li, Kai Way; Peng, Lu (Ergonomics, 2025)
Human-virtual object interaction is common in both entertainment and work settings. This study investigated the movement time (MT) and subjective rating of difficulty (SRD) for moving a virtual cuboid in a 3D space. The participants wore an augmented reality (AR) headset, picked up a virtual cuboid, and placed it on an assigned target. They rated the SRD of the task on a five-point scale. The effects of the 3D coordinate of the target, sex, and handedness on the MT were analysed. The error placement rate was also recorded. Significant effects of spatial coordinates were found on both MT and SRD. Both single- and two-stage MT modelling were conducted using segmented and unsegmented MT data, respectively. The insignificant prediction error between the models indicates that the two-stage MT model is not superior to the single-stage one. The findings of this study are beneficial to software designers in designing user-friendly AR applications. PRACTITIONER SUMMARY: This study explores the movement time, subjective rating of difficulty, and error placement rate in positioning a virtual object in a 3D space. Regression movement time models were developed using both unsegmented and segmented movement time data. The findings provide insightful perspectives for software designers in designing user-friendly augmented reality applications.